Doing fence sitting: a discursive analysis of clinical psychologists' constructions of mental health - Lofgren, Axel; Hewitt, Vanessa; das Nair, Roshan (Sage Publications, 2015)
A growing body of research indicates that the way health care professionals conceptualize mental health might have important clinical implications. We adopted a discursive psychology approach to explore clinical psychologists’ accounts of mental health and its effects. Semistructured interviews were conducted with 11 clinical psychologists in the East Midlands region of the United Kingdom. The participants constructed mental health through building up biological factors and psychosocial aspects as opposite ends of the same spectrum, and then positioned themselves as distant from these extremes to manage issues of stake and accountability. A discourse of moral concern for service users was used to negotiate the implications of having different views of mental health from service users, enabling clinicians to manage issues of accountability and demonstrate their ability to be helpful. This suggests that clinicians should be mindful of the effects of their use of language and make the contingent nature of their knowledge explicit.